Review of the book of Svetoslav P. Velchev “Public prosecutor’s supervision: Origin, development, functions” - Vuchkov, Veselin (Law Journal of New Bulgarian University, 2022)
The book review examines shortly the history of the public prosecutor’s supervision. The book is issued in а new format in 2021 by the Publishing House of the New Bulgarian University. The first edition of the book was in 1928 and its author was one of the most famous Bulgarian lawyers in the period before 1944 – Svetoslav Petrov Velchev (1870–1943). He held the position of Prosecutor General in the Supreme Court of Cassation (1920–1932) and was the first chairman of Supreme Administrative Court (1932–1938). Prof. Veselin Vuchkov is author of the biographical essay at the beginning of this new edition.